Early Model of Student's Graduation Prediction Based on Neural Network - Budi Rahmani; Hugo Aprilianto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Predicting  timing  of  student  graduation  would  be  a valuable  input  for  the  management  of  a  Department  at  a University. However, this is a difficult task if it is done manually.  With  the  help  of  learning  on  the  existing Artificial  Neural  Networks,  it  is  possible  to  provide training  with  a  certain  configuration,  in  which  based  on experience of previous graduate  data,  it would be possible to predict the time grouping of a student’s graduation. The input of  the system is the performance index  of  the first, second,  and  third  semester.  Based  on  testing  performed  on 166  data,  the  Artificial  Neural  Networks  that  have  been built were able to predict with up to 99.9% accuracy.